Fiscal austerity, unemployment and family firms - Zsuzsa Munkacsi (Deutsche Bundesbank, 2015)
I calculate unemployment multipliers of fiscal consolidation policies in a standard, closed-economy New Keynesian framework with search and matching frictions, and, as an innovation, in the presence of sectoral heterogeneity. Family and non-family firms behave differently in the labor market and are differently managed. This latter assumption is modeled by the inclusion of intangible capital in the family sector. The model is calibrated to match European data on countries with a large percentage of family firms in the labor force. I find that fiscal austerity raises unemployment. Both at peak and cumulatively, unemployment reacts least when the budget is consolidated by increasing the rate of value-added tax. At peak, the highest increase in unemployment is induced by a cut in government consumption, but, cumulatively, a hike in employees' labor income tax is just as costly in terms of employment. There are trade-offs, however, which a policymaker must face, as the value-added tax increase results in the steepest decline in consumption. Sectoral heterogeneity is crucial; multipliers of labor income tax policies and government consumption multipliers are usually biased downwards, while the consumption-tax multipliers are often biased upwards. Thus, ignoring sectoral heterogeneity might lead to incorrect policy conclusions.
Keywords: E22; E24; E62; J64; 330; fiscal austerity; government consumption; labor income tax; consumption tax; social security contribution; unemployment multiplier; sectoral heterogeneity; family firms; intangible capital